An Efficient Analytical Technique for Time-Fractional Parabolic Partial Differential Equations - Mustahsan, Muhammad; Younas, H. M.; Iqbal, S.; Rathore, Sushila; Nisar, Kottakkaran Sooppy; Singh, Jagdev (Frontiers in Physics, 2020)
In this work, we examine the time-fractional fourth-order parabolic partial differential equations with the aid of the optimal homotopy asymptotic method (OHAM). The 2nd order approximate results obtained by using the suggested scheme are compared with the exact solution. It has been noted that the results achieved via OHAM have a large convergence rate for the problems. The solutions are graphically analyzed, and the relative errors are presented in tabular form.